REVIEW ARTIKEL: GEN SITOKROM YANG MEMPENGARUHI EFEKTIVITAS OBAT KONTRASEPSI DAN BERHUBUNGAN DENGAN VENOUS THROMBOEMBOLISM (VTE) - Tamara, Aulia; Fibe Yulinda Cesa; Christina Agustin (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2025)
One cardiovascular condition known as venous thromboembolism (VTE) is believed to be brought on by hormonal medications like oral contraceptives. Women taking oral contraceptives are more likely to develop VTE over the age of 40 due to a genetic predisposition that can trigger the risk from the cytochrome gene. One of the genes associated with VTE and contraception is the CYP2C19, CYP3A4, CYP1A2, and CYP345 genes. Methods: A quality assessment of the method and risk was conducted using The Joanna Briggs Institute (JBI) Instrument after a number of articles collected from Scopus, Crossref, Ebsco, Pubmed, Science Direct, and Google Scholar were selected by the inclusion criteria. Results:Articles or journals on the JBI instrument showed good quality in the number of 10 research particles. From the results of the journal analysis, several cytochrome genes were obtained, namely the CYP2C19, CYP3A4, CYP1A2, and CYP345 genes. Conclusion: Several types of cytochrome genes that affect oral use as well as VTE. The cytochrome CYP2C19 gene may decrease the effects of clopidogrel. The use of CYP3A4 gene-inducing drugs should be considered at the same time as contraception and it is advisable to use other drug alternatives. Concomitant use of CYP1A2 gene-inducing drugs with contraception should be avoided because they may decrease the contraceptive effect. The use of cyclosporine drugs needs to be monitored because cyclosporine can increase estrogen levels in the liver.